PERAN KREATIVITAS KYAI DALAM PEMBENTUKAN NILAI RELIGIUS DAN MINAT BELAJAR ANAK DI PESANTREN PENDIDIKAN DASAR - Aisyah Chorijatun Nahri; Daimah; Nurzamsinar; Zainun Wafiqatun Niam (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Islamic boarding schools have a significant role in Islamic religious education in Indonesia. One of the key factors in the success of education in Islamic boarding schools is the role of kyai as caregivers and leaders. This research aims to examine the role of kyai creativity in increasing students' interest in learning. Through a qualitative approach, this research found that kyai creativity in teaching methods, personal approaches, and learning program innovation can significantly increase students' learning motivation. From the results of this research, it was found that many students are lazy about studying, therefore it is very necessary to emphasize the importance of creativity in educational leadership to build interest and motivation to learn.